Peningkatan Kualitas Pembelajaran Fisika di SMAN 2 Mataram Melalui Penerapan Pendekatan Keterampilan Proses - Ayub, Syahrial; Gunada, I Wayan; Afifah, Gusti (Jurnal Pendidikan Fisika dan Teknologi, 2019)
This collaborative action research which was aimed to improve the quality of physics teaching through the implementation curriculum of 2004 in teaching scenario which oriented for process skill. This action research was conducted to the second year students of The State Senior High School 2 Mataram, by involving two teachers for giving the treatmen. The data needed such as observation result of teaching inthe class and the student response were collected by observation format of teaching in the class and questionnare. By using quantitative and qualitative analysis, it was found that 1) the implementation of process skill teaching can quality improvement of physic teaching in The State Senior High School 2 Mataram, 2) student's response for implementation of process skill teaching is good, 3) the student's opinion toward implementation of process skill teaching is quantitatively positive. Based on this result, it is recommended that physic teacher implement process skill teaching of teaching continuosly in order to improve student's achievement.